Studi Pengaruh Konsentrasi dan Frekuensi Pemberian NAA Terhadap Pertumbuhan Tunas Stek Umbi Porang (Amorphohallus muelleri Blume) - Mora, Yun Fita; Rahmawati, Nini; Siregar, Luthfi A M (AGRIUM: Jurnal Ilmu Pertanian, 2026)
Increasing industrial demand for porang requires efficient propagation strategies, such as tuber cuttings combined with NAA application to enhance shoot and root development. This study aimed to evaluate the effects of NAA concentration and application frequency on the growth of porang tuber cuttings. The experiment was conducted from July to December 2024 in Pagar Merbau III Village, Lubuk Pakam District, and at the Biotechnology Laboratory, Faculty of Agriculture, University of North Sumatra, using a two-factor Randomized Block Design with three replications. The treatments consisted of four levels of NAA concentration (0, 50, 100, and 150 ppm) and two application frequencies (single application at the beginning of the nursery stage and repeated application at the beginning of the nursery stage and 7 days after sowing). Observed variables included shoot emergence percentage, plant growth, biomass, tuber weight, chlorophyll content, and stomatal density. Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test at a 5% significance level. The results showed that the application of NAA at 100 ppm significantly enhanced shoot growth, plant height, fresh and dry weight, chlorophyll content, and stomatal characteristics. A single application at the early nursery stage produced optimal results in plant height, tuber weight, and chlorophyll content, while repeated application increased the number of shoots, vegetative growth, and biomass accumulation. The interaction between 100 ppm NAA and early application resulted in the best performance in leaf number at 3 weeks after planting and tuber weight.